Implementasi Peraturan Menteri Pertanian Nomor 64 Tahun 2013 Tentang Sistem Pertanian Organik (Studi Pada Kota Batu) - Elvionita, Penti (Jurnal Administrasi Publik, 2014)
Abstract: Implementation Regulation of the Minister of Agriculture No. 64 Year 2013 on Organic Farming System (Kota Batu). In agricultural development, there are several issues about dependency of farmers using fertilizers and pesticides. To overcome these problems agriculture minister to make regulations about organic farming system. This study aims to determine, describe and analyze the implementation of the Regulation of the Minister of Agriculture No. 64 Year 2013 on Organic Farming System in Kota Batu. The results showed that implementation of the Minister of Agriculture Regulation No. 64 Year 2014 on Organic Farming System is in conformity with the Regulation of the Minister, but the government has yet to initiate development of the region that have natural resources that are not contaminated by the chemical. The benefits of this research to develop a theoretically existing theories on the implementation of rules, practically providing information in the field of agriculture and provide a reference in formulating policies in agriculture. Keywords: implementation, organic farming system Â  Abstrak: Implementasi Peraturan Menteri Pertanian Nomor 64 Tahun 2013 Tentang Sistem Pertanian Organik (Studi Pada Kota Batu). Dalam pengembangan pertanian terdapat beberapa permasalahan tentang ketergantungan petani menggunakan pupuk dan pestisida. Untuk mengatasi masalah tersebut pemerintah membuat peraturan menteri pertanian tentang sistem pertanian organik. Penelitian ini bertujuan untuk mengetahui, mendeskripsikan dan menganalisis mengenai Implementasi Peraturan Menteri Pertanian Nomor 64 Tahun 2013 tentang Sistem Pertanian Organik di Kota Batu. Hasil penelitian menunjukkan bahwa Implementasi Peraturan Menteri Pertanian Nomor 64 Tahun 2014 tentang Sistem Pertanian Organik sudah sesuai dengan Peraturan Menteri tetapi dalam pengembangannya pemerintah belum mengawali dari kawasan yang mempunyai SDA yang tidak terkontaminasi oleh kimia. Manfaat penelitian ini secara teoritis untuk mengembangkan teori yang sudah ada mengenai implementasi peraturan, secara praktis memberikan informasi dalam bidang pertanian dan memberikan referensi dalam menyusun kebijakan dalam bidang pertanian. Â  Kata kunci: implementasi, sistem pertanian organik